The Impact of the Private Security Industry Regulation Act and other Legislative Frameworks on Private Securities Operating in Drinking Establishments in South Africa - Modeccai Mbhele, Nkosingiphile; Mphatheni, Mandlenkosi Richard; Mlamla, Ntsika Edward; Singh, Shanta Balgobind (International Journal of Criminology and Sociology, 2022)
This paper seeks to explore the legislation and regulatory frameworks that guides the functionality and operation of private securities placed in drinking establishments in South Africa. Prior research has indicated lack of clarity regarding private security personnel regulation in drinking establishments, otherwise known as bouncers. For instance, the Private Security Industry Regulatory Authority (PSIRA) is the current regulatory structure which is mandated to monitor and regulate all the private security industries in South Africa. Private security players in South Africa are obligated to comply with the PSIR Act and related laws in general. For this reason, the duty of PSIRA to oversee and monitor private securities and to ensure that they comply with the law is paramount. However, a major concern is whether nightclub security is regulated in adherence to this Act or not. Research evidence has shown that security legislation and guidelines are either not in place or not enforced at nightclubs. The purpose of this article is to examine critical legislations that South African nightclub securities must comply with to ensure legitimacy. Furthermore, it assesses the regulatory body, PSIRA, in relation to South African nightclub securities. It further explores the training requirements needed to qualify as a nightclub security. Arguably, a limited number of studies address the skills and legal requirements nightclub securities need to meet to fully qualify to work as a nightclub security in South Africa. Thus this paper will add to the body of knowledge in the field of nightclub security regulation. Strengthening the regulatory framework and increasing the authority's enforcement capacity to regulate the industry more effectively have become inevitable obligations, especially in light of the continued growth in the private security industry. The article finds that nightclub security is not adequately regulated, leading to non-compliance of the regulatory framework from the private security industry. This paper is an extensive review of literature focusing on South African legislative frameworks that regulate private security operations in drinking establishments.